Analisis Minat dan Bakat Siswa pada Pembelajaran Biologi Kelas XI - Miza Nina Adlini; Celline Efrilia; Dewi Nurul Artika; Adelia Putri; Amanda Nurul Aisyah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Secondary education is the level of education for students to carry out educational activities. Secondary education is organized to continue and broaden the knowledge gained in primary and secondary schools, in addition to preparing students to become members of society who can interact with their environment, and their skills can be further developed in the world of work or further. their education. The research method that will be used in this study is a descriptive method with a qualitative approach. According to Mulyani et al (2021), qualitative research is research that aims to understand the phenomena experienced by research subjects Keywords : Education, interest in learning, student talent.